Preventif penyebaran penyakit Cacar (Monkeypox) yang menyerang kesehatan manusia - Azzahro, Salsa Billa Dwi; Damaia, Thifal Faza (Maliki Interdisciplinary Journal, 2024)
This article is motivated by the spread of monkey pox (monkeypox) which has become a hot topic of discussion by the public today. The purpose of writing this article is to illustrate how preventive efforts can be made to avoid the spread of the monkeypox virus. Monkey pox (monkeypox), is a viral infectious disease caused by orthopoxvirus. A person who has monkey pox experiences initial symptoms, namely headache, high fever, sore throat, and swollen lymph nodes. After the initial symptoms appear, it will be followed by the appearance of a red skin rash that spreads to all parts of the body. Preventive efforts that can be made to avoid the spread of monkey pox are by vaccinating, counseling the community, maintaining environmental hygiene, etc.